Shaping Immigration Narratives in Young Adult Literature: Authors and Paratextual Features of USBBY Outstanding International Books, 2006–2019. Issue 6 (20th April 2021) - Durand, E. Sybil; Glenn, Wendy J.; Moore, Daniel; Groenke, Susan L.; Scaramuzzo, Peter
Abstract: This article contributes to research on equity in award‐winning and honor books by offering a paratextual analysis of 14 immigration‐themed young adult books that were included on the USBBY Outstanding International Books list between 2006 and 2019. Findings reveal that paratexts—all parts of a book excluding the narrative—frame authors who are not members of the cultures they describe as having authority to tell immigration stories through authors' sociocultural proximity to real events and people who experienced migration. However, other paratextual features, such as titles, covers, and author interviews, reveal ideological problems in some authors' didactic purposes for telling immigration stories and disproportionately depict migration in terms of escape and rescue. For educators, this article invites a reconsideration of text selection processes relative to an author's background in connection to immigration and offers ideas for how teachers and their students might think critically about authorship.